Distribution of Helicobacter pylori infection and abnormal body- mass index (BMI) in a developing country - Basit Siddiqui; Javed Yakoob; Zaigham Abbas; Rabeea Azmat; Syeda Sadia Fatima; Safia Awan (Journal of Infection in Developing Countries)
Introduction: Helicobacter pylori is prevalent in developing nations. We determined the prevalence of H. pylori infection in relation to body-mass index (BMI) of dyspeptic patients and related comorbid conditions.